Quantification of [11C]PIB PET for Imaging Myelin in the Human Brain: A Test—Retest Reproducibility Study in High-Resolution Research Tomography. Issue 11 (November 2015) - Veronese, Mattia; Bodini, Benedetta; García-Lorenzo, Daniel; Battaglini, Marco; Bongarzone, Salvatore; Comtat, Claude; Bottlaender, Michel; Stankoff, Bruno; Turkheimer, Federico E
An accurate in vivo measure of myelin content is essential to deepen our insight into the mechanisms underlying demyelinating and dysmyelinating neurological disorders, and to evaluate the effects of emerging remyelinating treatments. Recently [ 11 C]PIB, a positron emission tomography (PET) tracer originally conceived as a beta-amyloid marker, has been shown to be sensitive to myelin changes in preclinical models and humans. In this work, we propose a reference-region methodology for the voxelwise quantification of brain white-matter (WM) binding for [ 11 C]PIB. This methodology consists of a supervised procedure for the automatic extraction of a reference region and the application of the Logan graphical method to generate distribution volume ratio (DVR) maps. This approach was assessed on a test–retest group of 10 healthy volunteers using a high-resolution PET tomograph. The [ 11 C]PIB PET tracer binding was shown to be up to 23% higher in WM compared with gray matter, depending on the image reconstruction. The DVR estimates were characterized by high reliability (outliers < 1%) and reproducibility (intraclass correlation coefficient (ICC) > 0.95). [ 11 C]PIB parametric maps were also found to be significantly correlated ( R 2 > 0.50) to mRNA expressions of the most represented proteins in the myelin sheath. On the contrary, no correlation was found between [ 11 C]PIB imaging and nonmyelin-associated proteins.